Industry Clusters and Innovation in the Arab World : Challenges and Opportunities. - El Ebrashi, Raghda (Emerald Publishing Limited, 2023)
Industry clusters promote innovation in the Arab World, through collaboration among businesses, research institutions, and governments. Benefits include the creation and sharing of knowledge, professional networking, access to spill-over knowledge, and specialized talent pools.